An investigation on the photovoltaic performance of quantum dot solar cells sensitized by CdTe, CdSe and CdS having comparable size. (May 2020) - Nideep, T.K.; Ramya, M.; Kailasnath, M.
Abstract: Quantum dot sensitized solar cells (QDSSC) have been fabricated with CdTe, CdSe and CdS quantum dots (QDs) of nearly similar size as the photosensitizers. The optical and structural characteristics were studied using absorption spectroscopy, XRD and TEM. Efficiency of the fabricated solar cells was found to improve by the incorporation of an additional buffer layer of ZnS. The value of efficiencies for the QDSSCs corresponding to the sensitizers CdTe, CdSe and CdS are 0.22%, 0.25% and 0.20%. After treatment with ZnS using SILAR cycle, an enhacement in the efficiency to 1.41%, 1.98% and 0.94% was noticed for the QDSSC sensitized with CdTe, CdSe and CdS QDs respectively. The differences in efficiencies as well as other photovoltaic parameters for the solar cells have been explained using the differences in effective masses of charge carriers and carrier lifetime in the three different QD samples. CdSe is found to have high adsorption property towards ZnS compared to CdTe or CdS QDs. Also, the ZnS buffer layer acts as a good agent for reducing the back scattering of electrons thereby improving the efficiency of all the three QD solar cells. Highlights: This is a unique study on the photovoltaic performance of QDSSC using the QDs of CdTe, CdSe, and CdS with comparable size. The variation in efficiency of the three QDSSC's was explained based on the effective mass. Effect of ZnS buffer layer on improving the efficiency of QDSSCs was also studied.